Cover crops and residual effect of lime and gypsum on soil subsurface physical attributes (Research, Society and Development, 2020)
The use of lime, gypsum, and different cover crops may influence the soil physical attributes, the formation of soil coverage before the crop implantation is crucial for the consolidation of the No-Tillage System. This work aimed to evaluate the alterations in the subsoil physical attributes, influenced by different cover crops combined with the application of lime and gypsum, in a no-tillage system in the Cerrado region, the soil of the experiment area was classified as Dystrophic Red Latosol. The experiment was carried out in Chapadão do Sul, state of Mato Grosso do Sul, Brazil, in a complete randomized block design, in a split-plot scheme. Plots consisted of cover crops (Urochloa ruziziensis and Pennisetum glaucum) and fallow; the subplots were formed by gypsum rates (0, 2.3, and 4.6 Mg ha-1); and the sub-sub-plots consisted of lime rates (0, 2, 4, and 6 Mg ha-1), with three replications. The cover crops, Uruchloa ruziziensis, Pennisetum glaucum and the rates of limestone and gypsum do not interfere with the density of the soil. The Uruchloa ruziziensis cover crop provides increased microporosity and total soil porosity. The cover crops Uruchloa ruziziensis and Pennisetum glaucum were not efficient in decompressing the soil in the layers of 0.20 - 0.30 and 0.30 - 0.40 m in depth. The residual effect of the lime rate of 2 Mg ha-1 without gypsum application provided higher total porosity the 0.30 - 0.40 m layer.